Characteristics of nurse practitioners and physician assistants in the United States. Issue 1 (January 2016) - Hooker, Roderick S.; Brock, Douglas M.; Cook, Michelle L.
Abstract : Background: : Nurse practitioners (NP) and physician assistants (PA) serve as independent or semiautonomous providers and as fundamental members of healthcare teams. Purpose: : Differentiating roles of health professionals is needed for optimal employment utilization. Clinically practicing PAs and NPs were characterized. Methodology: : Data included wage and workforce projections to 2022.Variables included number practicing, age, gender, race, ethnicity, education, principal employer, practice specialty, and wages. Results: : Health delivery establishments employed 88, 110 PA and 113, 370 NP clinicians in 2013. Both were predominantly female: NPs were older (49 years) on average than PAs (38 years). A significant number of them practiced in physicians' offices or in acute care hospitals. Median wages were at parity. Growth predictions from 2012 to 2022 were 31%–35%. Conclusions: : PAs and NPs constitute 20% of the composite clinician labor force (MD, DO, PA, NP). Labor market analysis suggests they are in demand. A majority of NPs and a third of PAs work in primary care fields. Their collective projected growth suggests a solution to emerging workforce shortages and an ability to help meet healthcare demands. Implications for practice: : Adaptability to changing roles, especially in primary care and underserved areas, makes them facile responders to market demands in a continuously evolving healthcare environment.